Effect of Foot Reflexology on Anxiety of Mothers of High Risk Neonates undergone Cesarean Section: a Non Randomized Controlled Trial - Farideh Bastani; Elaheh Rouhi Rahim Begloo; Hamid Haghani (Tehran University of Medical Sciences, 2015)
Background & Aim: Anxiety is associated with postpartum mood disorder; and is increased with birth of high risk neonates. Foot reflexology is a nursing intervention that can be used to reduce anxiety. T he aim of this study was to evaluate the effect of foot reflexology on anxiety in mothers with high risk neonates after Cesarean section s .   Methods & Materials: In this non-randomized clinical trial, 99 mothers having high risk neonates were recruited from the Women's General Hospital and Valieasr Hospital . The participants were allocated into three groups (n=33/group) using convenience sampling method . The group I received foot r eflexology for 40 minutes ; group II received leg massage ; and the control group received usual care after the Cesarean section. The Spielberger questionnaire was completed at baseline and three days after the interventions by the participants . Data were analyzed using the r epeated measure ANOVA and Chi-Squared in the SPSS-16 .    Results: At the baseline, there were no significant differences between the three groups in terms of demographic characteristics and the mean scores of anxiety . After the interventions, the mean score of anxiety was significantly lower in the reflexology and placebo groups than the control group (P<0.001). There was no significant difference between the reflexology and placebo groups in terms of the mean scores of anxiety (P>0.05). Comparing the mean score of anxiety between the reflexology (14.7±7.2) and placebo (9.4±8.5) groups indicated that the reflexology intervention was more effective in reducing anxiety .   Conclusion: The use of foot reflexology was effective in reducing anxiety. Nurses should use this non-pharmacologic method to control the symptoms of anxiety among mothers .